Legal Certainty of Land Registration as a Form of Protection of Citizens' Constitutional Rights - Fakhry Firmanto; Hafiz Sutrisno (Yayasan Pendidikan Islam Almatani, 2026)
This study examines the implementation of land registration services as a mechanism for protecting constitutional rights to legal certainty, focusing on the practice of the National Land Agency (BPN) of Kampar Regency under Government Regulation Number 18 of 2021. Using an empirical juridical approach, this research combines primary data obtained from interviews with BPN officials and land registration applicants with secondary data derived from statutory regulations, legal doctrines, and official documents. The findings reveal that, although land registration has formally functioned as an instrument of legal protection through the issuance of land certificates, its effectiveness in realizing constitutional legal certainty remains limited. Normative constraints arise from regulatory disharmony between the Basic Agrarian Law and Government Regulation Number 18 of 2021, while empirical obstacles include low public legal awareness, limited institutional capacity, and delays in land measurement procedures. These conditions indicate a gap between the normative objectives of land registration reform and its practical implementation at the local level. This study argues that the protection of constitutional rights in land administration cannot be achieved solely through regulatory reform, but requires regulatory harmonization, institutional strengthening, and sustained legal education to ensure the consistent application of legal certainty and substantive justice.